Correlation between structure and optical properties of lead metasilicate glass-ceramic under high hydrostatic pressures - Pena, Rafaella Bartz (2022)
Glass structures are determined by not only composition, pressure, and temperature but also by the pressure and thermal histories in which the glass was submitted. In this thesis, a systematic study of these variables was performed in undoped and cobalt-doped lead metasilicate (PbSiO3) glasses and mainly probed by Raman spectroscopy. High pressure was applied in a Diamond Anvil Cell (DAC), and the samples were studied ex-situ and in-situ. Ex-situ Raman investigation appoints for an unusual increase in the non-bridging oxygens (NBO) population, at the expense of the bridging oxygens (BO) population, leading to slight depolymerization of the densified metasilicate structure. In-situ investigation of this glass under pressure suggests the densification mechanisms occurring via the formation of an intermediary more polymerized state. Such modifications are accompanied by a change in the lead environment with the formation of highly coordinated PbOn polyhedra. High-temperature investigations were performed in isothermal and non-isothermal runs, providing evidence that the phase evolution from the glass to the stable alamosite is intermediated by two metastable crystalline phases, with a temperature-dependent crystallization path. For the same composition submitted to extremal conditions, the controlling of these structures may offer vast possibilities to tailor the glass-ceramic optical properties.